Preparing for an Aging World: The Case for Cross-National Research - National Research Council (The National Academies Press, 2001)
Aging is a process that encompasses virtually all aspects of life. Because the speed of population aging is accelerating, and because the data needed to study the aging process are complex and expensive to obtain, it is imperative that countries coordinate their research efforts to reap the most benefits from this important information. Preparing for an Aging World looks at the behavioral and socioeconomic aspects of aging, and focuses on work, retirement, and pensions; wealth and savings behavior; health and disability; intergenerational transfers; and concepts of well-being. It makes recommendations for a collection of new, cross-national data on aging populations2014data that will allow nations to develop policies and programs for addressing the major shifts in population age structure now occurring. These efforts, if made internationally, would advance our understanding of the aging process around the world.

Educating Children with Autism - National Research Council (The National Academies Press, 2001)
Autism is a word most of us are familiar with. But do we really know what it means? Children with autism are challenged by the most essential human behaviors. They have difficulty interacting with other people2014often failing to see people as people rather than simply objects in their environment. They cannot easily communicate ideas and feelings, have great trouble imagining what others think or feel, and in some cases spend their lives speechless. They frequently find it hard to make friends or even bond with family members. Their behavior can seem bizarre. Education is the primary form of treatment for this mysterious condition. This means that we place important responsibilities on schools, teachers and children's parents, as well as the other professionals who work with children with autism. With the passage of the Individuals with Disabilities Education Act of 1975, we accepted responsibility for educating children who face special challenges like autism. While we have since amassed a substantial body of research, researchers have not adequately communicated with one another, and their findings have not been integrated into a proven curriculum. Educating Children with Autism outlines an interdisciplinary approach to education for children with autism. The committee explores what makes education effective for the child with autism and identifies specific characteristics of programs that work. Recommendations are offered for choosing educational content and strategies, introducing interaction with other children, and other key areas. This book examines some fundamental issues, including: How children's specific diagnoses should affect educational assessment and planning How we can support the families of children with autism Features of effective instructional and comprehensive programs and strategies How we can better prepare teachers, school staffs, professionals, and parents to educate children with autism What policies at the federal, state, and local levels will best ensure appropriate education, examining strategies and resources needed to address the rights of children with autism to appropriate education. Children with autism present educators with one of their most difficult challenges. Through a comprehensive examination of the scientific knowledge underlying educational practices, programs, and strategies, Educating Children with Autism presents valuable information for parents, administrators, advocates, researchers, and policy makers.

Eager to Learn: Educating Our Preschoolers - National Research Council (The National Academies Press, 2001)
Clearly babies come into the world remarkably receptive to its wonders. Their alertness to sights, sounds, and even abstract concepts makes them inquisitive explorers2014and learners2014every waking minute. Well before formal schooling begins, children's early experiences lay the foundations for their later social behavior, emotional regulation, and literacy. Yet, for a variety of reasons, far too little attention is given to the quality of these crucial years. Outmoded theories, outdated facts, and undersized budgets all play a part in the uneven quality of early childhood programs throughout our country. What will it take to provide better early education and care for our children between the ages of two and five? Eager to Learn explores this crucial question, synthesizing the newest research findings on how young children learn and the impact of early learning. Key discoveries in how young children learn are reviewed in language accessible to parents as well as educators: findings about the interplay of biology and environment, variations in learning among individuals and children from different social and economic groups, and the importance of health, safety, nutrition and interpersonal warmth to early learning. Perhaps most significant, the book documents how very early in life learning really begins. Valuable conclusions and recommendations are presented in the areas of the teacher-child relationship, the organization and content of curriculum, meeting the needs of those children most at risk of school failure, teacher preparation, assessment of teaching and learning, and more. The book discusses: Evidence for competing theories, models, and approaches in the field and a hard look at some day-to-day practices and activities generally used in preschool. The role of the teacher, the importance of peer interactions, and other relationships in the child's life. Learning needs of minority children, children with disabilities, and other special groups. Approaches to assessing young children's learning for the purposes of policy decisions, diagnosis of educational difficulties, and instructional planning. Preparation and continuing development of teachers. Eager to Learn presents a comprehensive, coherent picture of early childhood learning, along with a clear path toward improving this important stage of life for all children.

Early Childhood Development and Learning: New Knowledge for Policy (The National Academies Press, 2001)

The American Community Survey: Summary of a Workshop - National Research Council (The National Academies Press, 2001)
The American Community Survey (ACS), to be run by the Census Bureau, will be a large (250,000 housing units a month), predominantly mailout\/mailback survey that will collect information similar to that on the decennial census long form. The development of this new survey raises interesting questions about methods used for combining information from surveys and from administrative records, weighting to treat nonresponse and undercoverage, estimation for small areas, sample design, and calibration of the output from this survey with that from the long form. To assist the Census Bureau in developing a research agenda to address these and other methodological issues, the Committee on National Statistics held a workshop on September 13, 1998. This report summarizes that workshop.

Classroom Assessment and the National Science Education Standards - National Research Council (The National Academies Press, 2001)
The National Science Education Standards address not only what students should learn about science but also how their learning should be assessed. How do we know what they know? This accompanying volume to the Standards focuses on a key kind of assessment: the evaluation that occurs regularly in the classroom, by the teacher and his or her students as interacting participants. As students conduct experiments, for example, the teacher circulates around the room and asks individuals about their findings, using the feedback to adjust lessons plans and take other actions to boost learning. Focusing on the teacher as the primary player in assessment, the book offers assessment guidelines and explores how they can be adapted to the individual classroom. It features examples, definitions, illustrative vignettes, and practical suggestions to help teachers obtain the greatest benefit from this daily evaluation and tailoring process. The volume discusses how classroom assessment differs from conventional testing and grading-and how it fits into the larger, comprehensive assessment system.

America Becoming: Racial Trends and Their Consequences: Volume II - National Research Council
The 20th Century has been marked by enormous change in terms of how we define race. In large part, we have thrown out the antiquated notions of the 1800s, giving way to a more realistic, sociocultural view of the world. The United States is, perhaps more than any other industrialized country, distinguished by the size and diversity of its racial and ethnic minority populations. Current trends promise that these features will endure. Fifty years from now, there will most likely be no single majority group in the United States. How will we fare as a nation when race-based issues such as immigration, job opportunities, and affirmative action are already so contentious today? In America Becoming, leading scholars and commentators explore past and current trends among African Americans, Hispanics, Asian Americans, and Native Americans in the context of a white majority. This volume presents the most up-to-date findings and analysis on racial and social dynamics, with recommendations for ongoing research. It examines compelling issues in the field of race relations, including: Race and ethnicity in criminal justice. Demographic and social trends for Hispanics, Asian Americans, and Native Americans. Trends in minority-owned businesses. Wealth, welfare, and racial stratification. Residential segregation and the meaning of \

Knowing What Students Know: The Science and Design of Educational Assessment - National Research Council (The National Academies Press, 2001)
Education is a hot topic. From the stage of presidential debates to tonight's dinner table, it is an issue that most Americans are deeply concerned about. While there are many strategies for improving the educational process, we need a way to find out what works and what doesn't work as well. Educational assessment seeks to determine just how well students are learning and is an integral part of our quest for improved education. The nation is pinning greater expectations on educational assessment than ever before. We look to these assessment tools when documenting whether students and institutions are truly meeting education goals. But we must stop and ask a crucial question: What kind of assessment is most effective? At a time when traditional testing is subject to increasing criticism, research suggests that new, exciting approaches to assessment may be on the horizon. Advances in the sciences of how people learn and how to measure such learning offer the hope of developing new kinds of assessments-assessments that help students succeed in school by making as clear as possible the nature of their accomplishments and the progress of their learning. Knowing What Students Know essentially explains how expanding knowledge in the scientific fields of human learning and educational measurement can form the foundations of an improved approach to assessment. These advances suggest ways that the targets of assessment-what students know and how well they know it-as well as the methods used to make inferences about student learning can be made more valid and instructionally useful. Principles for designing and using these new kinds of assessments are presented, and examples are used to illustrate the principles. Implications for policy, practice, and research are also explored. With the promise of a productive research-based approach to assessment of student learning, Knowing What Students Know will be important to education administrators, assessment designers, teachers and teacher educators, and education advocates.

Choosing the Right Formula: Initial Report - National Research Council (The National Academies Press, 2001)
The workshop was a direct outgrowth of a previous study by the CNSTAT Panel on Estimates of Poverty for Small Geographic Areas. That panel, established under a 1994 act of Congress, began its work with a very specific mission: to evaluate the suitability of the U.S. Census Bureau's small-area estimates of poor school-age children for use in the allocation of funds to counties and school districts under Title I of the Elementary and Secondary Education Act. In carrying out their assignment, panel members came to realize that the properties of data sources and statistical procedures used to produce formula estimates, interacting with formula features such as thresholds and hold-harmless provisions, can produce consequences that may not have been anticipated or intended. It also became evident that there is a trade-off between the goals of providing a reasonable amount of stability in funding from one year to the next and redirecting funds to different jurisdictions as true needs change. In one instance, for example, the annual appropriation included a 100 percent hold-harmless provision, ensuring that no recipient would receive less than the year before. However, there was no increase in the total appropriation, with the result that new estimates showing changes in the distribution of program needs across areas had no effect on the allocations. Choosing the Right Formula provides an account of the presentations and discussions at the workshop. The first three chapters cover the overview, case studies, and methodological sessions, respectively. Chapter 4 summarizes the issues discussed in the roundtable and concluding sessions, with emphasis on the identification of questions that might be addressed in a panel study.

America Becoming: Racial Trends and Their Consequences: Volume I - National Research Council
The 20th Century has been marked by enormous change in terms of how we define race. In large part, we have thrown out the antiquated notions of the 1800s, giving way to a more realistic, sociocultural view of the world. The United States is, perhaps more than any other industrialized country, distinguished by the size and diversity of its racial and ethnic minority populations. Current trends promise that these features will endure. Fifty years from now, there will most likely be no single majority group in the United States. How will we fare as a nation when race-based issues such as immigration, job opportunities, and affirmative action are already so contentious today? In America Becoming, leading scholars and commentators explore past and current trends among African Americans, Hispanics, Asian Americans, and Native Americans in the context of a white majority. This volume presents the most up-to-date findings and analysis on racial and social dynamics, with recommendations for ongoing research. It examines compelling issues in the field of race relations, including: Race and ethnicity in criminal justice. Demographic and social trends for Hispanics, Asian Americans, and Native Americans. Trends in minority-owned businesses. Wealth, welfare, and racial stratification. Residential segregation and the meaning of \

Proceedings, First Workshop: Panel to Review the 2000 Census - National Research Council (The National Academies Press, 2001)

Getting to Positive Outcomes for Children in Child Care: A Summary of Two Workshops - National Research Council; Institute of Medicine (The National Academies Press, 2001)
As a result of the heightened public and political attention and the movement toward standards and accountability, performance measurement has emerged as an important concern in the early childhood care and education field. At the request of the Department of Health and Human Services' Administration for Children and Families, the Board on Children, Youth, and Families convened two workshops to learn from existing efforts to develop performance measures for early childhood care and education, to consider what would be involved in developing and implementing an effective performance measurement system for this field, and to delineate some critical next steps for moving such an effort forward.

Adding It Up: Helping Children Learn Mathematics - National Research Council (The National Academies Press, 2001)
Adding It Up explores how students in pre-K through 8th grade learn mathematics and recommends how teaching, curricula, and teacher education should change to improve mathematics learning during these critical years. The committee identifies five interdependent components of mathematical proficiency and describes how students develop this proficiency. With examples and illustrations, the book presents a portrait of mathematics learning: Research findings on what children know about numbers by the time they arrive in pre-K and the implications for mathematics instruction. Details on the processes by which students acquire mathematical proficiency with whole numbers, rational numbers, and integers, as well as beginning algebra, geometry, measurement, and probability and statistics. The committee discusses what is known from research about teaching for mathematics proficiency, focusing on the interactions between teachers and students around educational materials and how teachers develop proficiency in teaching mathematics.

Diffusion Processes and Fertility Transition: Selected Perspectives - National Research Council (The National Academies Press, 2001)
This volume is part of an effort to review what is known about the determinants of fertility transition in developing countries and to identify lessons that might lead to policies aimed at lowering fertility. It addresses the roles of diffusion processes, ideational change, social networks, and mass communications in changing behavior and values, especially as related to childbearing. A new body of empirical research is currently emerging from studies of social networks in Asia (Thailand, Taiwan, Korea), Latin America (Costa Rica), and Sub-Saharan Africa (Kenya, Malawi, Ghana). Given the potential significance of social interactions to the design of effective family planning programs in high-fertility settings, efforts to synthesize this emerging body of literature are clearly important.

New Horizons in Health: An Integrative Approach - National Research Council (The National Academies Press, 2001)
New Horizons in Health discusses how the National Institutes of Health (NIH) can integrate research in the social, behavioral, and biomedical sciences to better understand the causes of disease as well as interventions that promote health. It outlines a set of research priorities for consideration by the Office of Behavioral and Social Sciences Research (OBSSR), with particular attention to research that can support and complement the work of the National Institutes of Health. By addressing the range of interactions among social settings, behavioral patterns, and important health concerns, it highlights areas of scientific opportunity where significant investment is most likely to improve national2014and global2014health outcomes. These opportunities will apply the knowledge and methods of the behavioral and social sciences to contemporary health needs, and give attention to the chief health concerns of the general public.

NAEP Reporting Practices: Investigating District-Level and Market-Basket Reporting - National Research Council (The National Academies Press, 2001)
At the request of the Department of Education, the National Research Council formed the Committee on NAEP Reporting Practices to address questions about the desirability, feasibility, and potential impact of implementing these reporting practices. The committee developed study questions designed to address issues surrounding district-level and market-basket reporting.

Understanding Dropouts: Statistics, Strategies, and High-Stakes Testing - National Research Council (The National Academies Press, 2001)
The role played by testing in the nation's public school system has been increasing steadily2014and growing more complicated2014for more than 20 years. The Committee on Educational Excellence and Testing Equity (CEETE) was formed to monitor the effects of education reform, particularly testing, on students at risk for academic failure because of poverty, lack of proficiency in English, disability, or membership in population subgroups that have been educationally disadvantaged. The committee recognizes the important potential benefits of standards-based reforms and of test results in revealing the impact of reform efforts on these students. The committee also recognizes the valuable role graduation tests can potentially play in making requirements concrete, in increasing the value of a diploma, and in motivating students and educators alike to work to higher standards. At the same time, educational testing is a complicated endeavor, that reality can fall far short of the model, and that testing cannot by itself provide the desired benefits. If testing is improperly used, it can have negative effects, such as encouraging school leaving, that can hit disadvantaged students hardest. The committee was concerned that the recent proliferation of high school exit examinations could have the unintended effect of increasing dropout rates among students whose rates are already far higher than the average, and has taken a close look at what is known about influences on dropout behavior and at the available data on dropouts and school completion.

Testing Teacher Candidates: The Role of Licensure Tests in Improving Teacher Quality - National Research Council (The National Academies Press, 2001)
Americans have adopted a reform agenda for their schools that calls for excellence in teaching and learning. School officials across the nation are hard at work targeting instruction at high levels for all students. Gaps remain, however, between the nation's educational aspirations and student achievement. To address these gaps, policy makers have recently focused on the qualifications of teachers and the preparation of teacher candidates. This book examines the appropriateness and technical quality of teacher licensure tests currently in use, evaluates the merits of using licensure test results to hold states and institutions of higher education accountable for the quality of teacher preparation and licensure, and suggests alternatives for developing and assessing beginning teacher competence. Teaching is a complex activity. Definitions of quality teaching have changed and will continue to change over time as society's values change. This book provides policy makers, teacher testers, and teacher educators with advice on how to use current tests to assess teacher candidates and evaluate teacher preparation, ensuring that America's youth are being taught by the most qualified candidates.

Adolescent Risk and Vulnerability: Concepts and Measurement - Institute of Medicine; National Research Council (The National Academies Press, 2001)
Adolescents obviously do not always act in ways that serve their own best interests, even as defined by them. Sometimes their perception of their own risks, even of survival to adulthood, is larger than the reality; in other cases, they underestimate the risks of particular actions or behaviors. It is possible, indeed likely, that some adolescents engage in risky behaviors because of a perception of invulnerability2014the current conventional wisdom of adults' views of adolescent behavior. Others, however, take risks because they feel vulnerable to a point approaching hopelessness. In either case, these perceptions can prompt adolescents to make poor decisions that can put them at risk and leave them vulnerable to physical or psychological harm that may have a negative impact on their long-term health and viability. A small planning group was formed to develop a workshop on reconceptualizing adolescent risk and vulnerability. With funding from Carnegie Corporation of New York, the Workshop on Adolescent Risk and Vulnerability: Setting Priorities took place on March 13, 2001, in Washington, DC. The workshop's goal was to put into perspective the total burden of vulnerability that adolescents face, taking advantage of the growing societal concern for adolescents, the need to set priorities for meeting adolescents' needs, and the opportunity to apply decision-making perspectives to this critical area. This report summarizes the workshop.

Knowing and Learning Mathematics for Teaching: Proceedings of a Workshop - National Research Council (The National Academies Press, 2001)
There are many questions about the mathematical preparation teachers need. Recent recommendations from a variety of sources state that reforming teacher preparation in postsecondary institutions is central in providing quality mathematics education to all students. The Mathematics Teacher Preparation Content Workshop examined this problem by considering two central questions: What is the mathematical knowledge teachers need to know in order to teach well? How can teachers develop the mathematical knowledge they need to teach well? The Workshop activities focused on using actual acts of teaching such as examining student work, designing tasks, or posing questions, as a medium for teacher learning. The Workshop proceedings, Knowing and Learning Mathematics for Teaching, is a collection of the papers presented, the activities, and plenary sessions that took place.